First Jurassic grasshopper (Insecta, Caelifera) from China - Gu, Jun-Jie; Yue, Yanli; Shi, Fuming; Tian, He; Ren, Dong (Zootaxa, 2016)
Orthoptera is divided into two suborders, the Ensifera (katydids, crickets and mole crickets) and the Caelifera (grasshoppers and pygmy mole crickets). The earliest definitive caeliferans are those found in the Triassic (Bethoux & Ross 2005). The extinct caeliferan families, such as Locustopsidae and Locustavidae, may prove to be stem groups to some of the modern superfamilies (Grimaldi & Engel 2005). Locustopsidae is known from the Late Triassic or Early Jurassic to Late Cretaceous, consisting of two subfamilies (Gorochov et al. 2006). They are recorded from Europe, England, Russia, central Asia, China, Egypt, North America, Brazil and Australia. Up to now, Late Mesozoic fossil deposits of China has been reported plenty taxa of orthopterids, e.g. ensiferans, phasmatodeans, grylloblattids (Cui et al. 2012; Gu et al. 2010; Gu et al. 2012a; Gu et al. 2012b; Ren et al. 2012; Wang et al. 2014); but, with few caeliferans records, only four species, Pseudoacrida costata Lin 1982, Mesolocustopsis sinica Hong 1990, Tachacris stenosis Lin 1977 and T. turgis Lin 1980, were reported from the Early Cretaceous of Ningxia, Shandong, Yunnan and Zhejiang of China.